PELAKSANAAN UNDANG-UNDANG NOMOR 41 TAHUN 2004 TENTANG WAKAF DALAM PENGELOLAANNYA DI KECAMATAN LAWEYAN KOTA SURAKARTA - WAHYUNINGSIH, EKO (Dinamika Hukum, 2018)
This study aims to determine the implementation of Law Number 41 of 2004 concerning Waqf in the Management of Waqf Land in Laweyan District, Surakarta City, the efforts made, the constraints faced and the solutions made in the implementation of the law. Sources of data in this study were collected through observation, interviews, and documentation obtained from the Head of the Office of Religious Affairs, Nazhir Wakaf, Wakif and Camat District Laweyan Surakarta City. Data analysis techniques used qualitative data analysis which was presented in descriptive form and conclusion drawing was done using the deductive method. From the research carried out, it was found that Law No. 41 of 2004 had not been fully implemented. Of the 169 waqf lands that have been pledged to represent 163 waqf lands. Likewise, the 8 existing waqf lands do not have a waqf certificate. In the case of Nazhir it was also found that some had not carried out their duties and functions according to the mandate of Law Number 41 of 2004 concerning Waqf. It was also found that there were 2 cases of waqf disputes. Some efforts have been made in the implementation of Law Number 41 of 2004 concerning Waqf in Laweyan Sub-District, Surakarta City, such as the dissemination of endowments and waqf certification. In the Implementation of Law Number 41 of 2004 concerning Waqf in Laweyan District, obstacles were still found, namely the lack of understanding of both waqif and Nazhir people regarding the law, the lack of orderly administration and management of waqf, the lack of knowledge of Nazhir in the endowments of waqf, and the abundance of land or the building that is represented does not have a land or building certificate. Overcoming these constraints The Head of the Office of Religious Affairs in Laweyan Subdistrict made a solution by appealing to the waqf, Nazhir, the Village Chief and the community to immediately make a Waqf Pledge Deed or Substitute Deed of Waqf Pledge, and free the waqf certification fee by charging it in the APBN. Keywords: waqf management